The Importance of Product Design and Its Role in Innovation, Marketing and Consumers’ Preferences of Product - Mahmad Hasan H (Universitas Komputer Indonesia, 2022)
Nowadays, there have been significant and considerable increments in the employment of product design in many companies, societies and fields. Product design has become an important tool for the growing of the image of the brand or trademark. The effective role of product design in the development of new product has been established. Product design has an influential effect on the marketing of any products. Also, product design has critical role in the judgment and decision making of consumers toward any product. In addition, innovation of designs has significant and positive effects on the performance of manufacturing. Thus, the aim of this paper is to review and evaluate the design importance, innovation, marketing and the factors that affecting the consumers’ preferences toward the design.